NEUROPHYSIOLOGICAL CHARACTERISTICS OF THE CONDITION OF PATIENTS WITH IDIOPATHIC SCOLIOSIS IN THE EARLY POSTOPERATIVE PERIOD - G. T. Kasimova; J.A. Nazarova (International Scientific and Current Research Conferences, 2021)
In this article, a retrospective analysis of complications in the early postoperative period was conducted in 57 patients with idiopathic infantile and juvenile breast scoliosis. During the surgical treatment of scoliosis, a variety of pathological syndromes of damage to the nervous system can occur. As can be seen from the study, in patients who underwent anterior mobilization and anterolateral epiphysiodesis of the thoracic spine as a separate stage of surgical treatment, neurological disorders were more pronounced and were observed in a larger number of patients than with combined surgical tactics.